MENIMBANG DEMOKRASI DELIBERATIF DALAM PROSES PEMBENTUKAN HUKUM YANG DEMOKRATIS DI INDONESIA - Sukma, Fadjar; Saparuli (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2021)
Citizens as subjects as well as objects of law have an important role in the process of forming laws that apply as a model that becomes patterns of interaction in the life of the state and society as well as an order of behavior that must be fulfilled. This is also in line with the latent spirit of the Indonesian nation, namely